Inside Back Cover: Synthesis of Highly Uniform Molybdenum–Glycerate Spheres and Their Conversion into Hierarchical MoS2 Hollow Nanospheres for Lithium‐Ion Batteries (Angew. Chem. Int. Ed. 26/2016). Issue 26 (20th May 2016) - Wang, Yawen; Yu, Le; Lou, Xiong Wen (David)
Abstract : A self‐templating method has been developed to synthesize hierarchical MoS2 hollow nanospheres from highly uniform Mo–glycerate solid spheres. In their Communication onpage 7423 ff. X. W. Lou and co‐workers first synthesize Mo–glycerate spheres with readily tunable sizes by a solvothermal process. The subsequent hierarchical MoS2 structures are formed from ultrathin subunits, have a hollow interior, and give a promising performance as the anode material for lithium‐ion batteries.